2014
DOI: 10.1177/1094670514543149
|View full text |Cite
|
Sign up to set email alerts
|

How Much Compensation Should a Firm Offer for a Flawed Service? An Examination of the Nonlinear Effects of Compensation on Satisfaction

Abstract: This research examines the nonlinear effects of compensation on customer satisfaction in order to determine the optimal compensation after a flawed service. As our core contribution, we argue that the nature of this nonlinear effect depends on the way customers handle a flawed service. Building on the Service-Dominant (S-D) logic, this research introduces two specific failure handling tactics-when customers reject versus accept a flawed value proposition-that affect the shape of the nonlinear function of compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
105
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(123 citation statements)
references
References 55 publications
11
105
0
4
Order By: Relevance
“…The practical implication for service providers is that a combination of apology and compensation is essential to effectively drive consumer forgiveness and lower NWOM intention. The results corroborate the recent trend in managerial practices to offer combined benefits of apologies and compensation to reduce customers' negative reactions following service failure (Gelbrich et al, 2015;Noone and Lee, 2011).…”
Section: Managerial Implicationssupporting
confidence: 89%
“…The practical implication for service providers is that a combination of apology and compensation is essential to effectively drive consumer forgiveness and lower NWOM intention. The results corroborate the recent trend in managerial practices to offer combined benefits of apologies and compensation to reduce customers' negative reactions following service failure (Gelbrich et al, 2015;Noone and Lee, 2011).…”
Section: Managerial Implicationssupporting
confidence: 89%
“…Furthermore, within the service failure literature, our study contributes to research on appropriate service recovery strategies (Gelbrich, Gäthke, and Grégoire 2015). An important determining factor of customers' satisfaction with service recovery is the confirmation of customers' expectations of this recovery (McCollough, Berry, and Yadav 2000).…”
Section: Research Issuesmentioning
confidence: 99%
“…This is regretful because the perceived fairness of a low‐price guarantee might have an influence on customers' repurchase intentions. In this light, recent overcompensation studies have found that fairness perceptions mediate the relationship between overcompensation and customer satisfaction (see Gelbrich et al, ). Therefore, in the present research we also investigated if and how fairness perceptions influence the effectiveness of different low‐price guarantees.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, scholars have tried to resolve these mixed results by systematically studying the overcompensation range by examining the influence of multiple refund depth levels. Gelbrich, Gäthke, and Grégoire (), for instance, compared five overcompensation levels (i.e., a compensation that covered 120%, 140%, 160%, 180%, and 200% of the loss) that a company could offer for a flawed service. Their results revealed a nonlinear effect of overcompensation on customer satisfaction in the form of a concave curve: Small amounts of overcompensation were more effective than an exact compensation, but after a certain point the curve seemed to flatten.…”
Section: Introductionmentioning
confidence: 99%